A study of situational awareness in a small group of sea kayaking guides. Issue 3 (3rd July 2021) - Collins, Loel; Giblin, Matthew; Stoszkowski, John Robert; Inkster, Allison
ABSTRACT: Situational awareness, which informs the decisions made by sea kayaking guides, is a critical safety factor in guided sea kayaking experiences. This study examines the situational awareness of a group of sea kayak guides operating in moderate water conditions. Utilising virtual reality technology, a freeze probe technique was employed with a small group of sea kayak guides. The findings suggest that the guides' recognition and understanding of key informational cues lacked both comprehension of their meaning and the ability to project their future impact on the situation. It is proposed that sea kayaking guide training needs to provide better comprehension of the (emerging) situations guides may experience as well as a capacity to predict the potential impacts of those situations. Improvements in metacognition and perception/action associations, rather than simple attention to the situation, are also a useful potential avenue to explore.